Clinical mesenchymal stem cell products experience functional changes in response to freezing - Pollock, Kathryn (Cytotherapy, 2014)
BACKGROUND: Current methods of MSC cryopreservation result in variable post thaw recovery and phenotypic changes due to freezing. The objective of this investigation is to determine the influence of ex-vivo cell expansion on phenotype of MSCs and the response of resulting phenotypes to freezing and thawing. METHODS: Human bone marrow aspirate was purchased from Lonza (Walkersville, MD). MSCs were isolated, and cells were assessed for total count, viability, apoptosis, and senescence over 6 passages (8–10 doublings/passage) in ex vivo culture. One half of cells harvested at each passage were re-plated for continued culture, and the other half were frozen at 1°C/min in a controlled rate freezer. Frozen samples were stored in liquid nitrogen, thawed, and reassessed for total cell count, viability, and senescence immediately and 48 hours post thaw. RESULTS: Viability did not differ significantly between samples pre freeze or post thaw. Senescence increased over time in pre freeze culture, and was significantly higher in one sample that experienced growth arrest both pre freeze and post thaw. Freezing resulted in similar initial post thaw recovery in all samples, but 48 hour post thaw growth arrest was observed in the sample with high senescence only. CONCLUSION: High freeze senescence appears to correlate with poor post thaw function in MSC samples, but additional studies are necessary to obtain a sample size large enough to quantify results.